Pengaruh Literasi Keuangan, Perilaku Keuangan, Pendapatan dan Motivasi terhadap Keputusan Investasi - Safitri, Risky Dian; Herman, Herman (Jurnal Ekonomi & Bisnis, 2024)
Investment decisions are needed to help novice investors in choosing investments that will be selected correctly and well. This research aims to provide empirical evidence about the influence of financial literacy, financial behavior, income and investment motivation on investment decisions. The type of research used is quantitative. The data analysis technique used in this research is multiple linear regression assisted by the SPSS version 26 application. The population in this research are students majoring in Accounting at STIE Balikpapan for the period 2020 - 2022. The sampling technique used in this research is by using a purposive sampling method with a total sample of 58 students. The results of this research show that financial literacy, financial behavior and income each partially have a positive and significant effect on investment decisions. Partial investment motivation has no negative and insignificant effect on investment decisions. The research results also show that financial literacy, financial behavior, income and investment motivation simultaneously have a significant influence on investment decisions. If financial literacy, financial behavior, income and investment motivation increase, then investment decisions will also increase, vice versa too.